Factors Affecting Food Safety of Animal Origin in Indonesia - Bahri, Sjamsul; Sani, Yulvian; ., Indraningsih (Indonesian Bulletin of Animal and Veterinary Sciences, 2006)
Based on the Indonesian Regulation Number 7 year 1996, food is defined as everything derived from biological sources and water, either processed and non-processed materials to be used as food and drinks, including food additives, food raw materials and other materials for preparation process, processing and production of food or drinks . Furthermore, food safety is a condition and an approach required to prevent the food from contamination of pathogenic microbes, toxic compounds and other xenobiotics that may affect and hazardous to human health . Food safety is basically a complexity and close related to policy . toxicity, microbiology, chemicals, nutrition status, health and public welfare . On the other hand, food safety problem is a dynamic process following the changing of public society including socioculture, health, development of science and technology as well as everything related to human life . In general, there are three main stages of process as the critical point in food safety of animal origin, namely : (1) preharvest ; (2) production ; and (3) postharvest . The main factors of these stages are discussed in this paper . Â  Key words : Food safety, livestock, preharvest, harvest, post harvest